Let p and q be distinct integers such that 1 9 8 1 + p = q 2 and 1 9 8 1 + q = p 2 . Find the value of 1 9 9 0 + p q .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
for p in range(-1000,10000):
for q in range(-1000,10000):
if (1981+p==q*q):
if (1981+q==p*p):
print (p,q)
Output:
-45 44
44 -45
In both cases, p q = − 1 9 8 0
⟹ 1 9 9 0 − 1 9 8 0 = 1 0
You are taking the assumption that − 1 0 0 0 < p < 1 0 0 0 0 ; − 1 0 0 0 < q < 1 0 0 0 0 which may or may not be true. Also try to solve these questions without calculators and computers it will develop your mathematical skills.
In PRMO, you aren't allowed to use a computer, or any computing device. It is better if you try to solve algebraically like @Zakir Husain
1 9 8 1 + p = q 2 . . . . . . . [ 1 ] 1 9 8 1 + q = p 2 . . . . . . . [ 2 ] [ 2 ] − [ 1 ] ⇒ q − p = p 2 − q 2 = ( p − q ) ( p + q ) As p and q are distinct ⇒ p − q = 0 ⇒ ( p + q ) = p − q q − p = − 1 ⇒ p + q = − 1 ⇒ p = − ( q + 1 ) Putting this in [ 1 ] 1 9 8 1 − q − 1 = q 2 1 9 8 0 = ( q 2 + q ) p q = − ( q + 1 ) q = − ( q 2 + q ) = − 1 9 8 0 1 9 9 0 + p q = 1 9 9 0 − 1 9 8 0 = 1 0
@Zakir Husain , now it's fine. And it's great that you mentioned distinct integers, otherwise, there is another solution: p = q ≈ 4 5 . 0 1 1
@Zakir Husain , Pre-RMO question 18!
Log in to reply
@Mahdi Raza - A Pre-RMO question! -18
Log in to reply
@Zakir Husain , I can't find any integer. Is the problem correct?
Log in to reply
@Mahdi Raza – Yes the problem is correct and there exists such integers
@Zakir Husain I cannot read any of the comments you are writing
Problem Loading...
Note Loading...
Set Loading...
Given that { 1 9 8 1 + p = q 2 1 9 8 1 + q = p 2 . . . ( 1 ) . . . ( 2 )
( 1 ) − ( 2 ) : p − q ⟹ p + q q q 2 − p 2 = ( q − p ) ( q + p ) = − 1 = − ( p + 1 )
( 1 ) : 1 9 8 1 + p 1 9 8 1 + p p 2 + p p ( p + 1 ) − p q p q ⟹ 1 9 9 0 + p q = ( − ( p + 1 ) ) 2 = p 2 + 2 p + 1 = 1 9 8 0 = 1 9 8 0 = 1 9 8 0 = − 1 9 8 0 = 1 9 9 0 − 1 9 8 0 = 1 0 Note that q = − ( p + 1 )